22‐1: Image Enhancement with Visual Saturation Preserving on Adaptive Histogram Model. Issue 1 (29th May 2019) - Shi, Chaochao; Jin, Yufeng; Chen, Yinhung; Zhao, Bin
Abstract : A novel algorithm based on histogram equalization (HE) is proposed, which has saturation preservation and obtain more suitable visual perception. This method can solve the problem of visual perception saturation decrease and color distortion caused by conventional histogram methods. The results show excellent performance in LDR image enhancement.